Three new species of Polystichum (Dryopteridaceae) from Xizang, China based on morphological and molecular evidence - Qiu, Yong-Ling; Yang, Jian-Jun; Zhou, Xin-Mao; Ju, Wen-Bin; Zhang, Li-Bing; He, Zhao-Rong; Zhang, Liang (Phytotaxa, 2023)
Three new species of the shield fern genus, Polystichum sunhangii, P. wusugongii, and P. xinfeniae, were described based on morphological and molecular evidence. The new species were discovered in Medog county, Xizang, at elevations ranging from 1200 to 2300 meters. The differences between each new species and their morphologically similar species were discussed. A phylogenetic analysis, based on five plastid markers, confirmed the recognition of the three new species in addition to their morphology.